Salvage Surgery for Thoracic SMARCA4-Deficient Undifferentiated Tumor - Masatoshi Kanayama, MD, PhD; Akihiro Taira, MD; Katsuma Yoshimatsu, MD; Hiroki Matsumiya, MD; Masataka Mori, MD, PhD; Masaru Takenaka, MD, PhD; Koji Kuroda, MD, PhD; Aya Nawata, MD, PhD; Fumihiro Tanaka, MD, PhD (Annals of Thoracic Surgery Short Reports)
Thoracic SMARCA4-deficient undifferentiated tumors (SMARCA4-UT) may be effectively managed with immune checkpoint inhibitors; however, the management of posttreatment exacerbations remains uncertain. A 48-year-old man underwent chemotherapy (cisplatin and pemetrexed) along with PD-L1 and CTLA-4 inhibitors, resulting in significant improvement. Subsequently, maintenance therapy was initiated but discontinued because of drug-induced pneumonia. Although prednisone treatment resolved the pneumonia, salvage surgery was performed for exacerbation of an enlarged chest tumor and lymph nodes. No additional postoperative treatment was administered, and the patient has completed 2.5 years of treatment. This case highlights the potential efficacy of salvage surgery in the management of SMARCA4-UT exacerbations.